Concentrations of Heavy Metals Pb and Cd in Porites lutea Coral in Mandalika Coastal Waters - Zahara, Asha Aulia; Candri, Dining Aidil; Ahyadi, Hilman; Rahayu, Rachmawati Noviana; Suana, I Wayan (JURNAL BIOS LOGOS, 2025)
The Mandalika Coastal Area, located in Central Lombok Regency, is a row of beaches and bays that have a large coral reef ecosystem and intertidal zone area. The increasing growth of activities on the Mandalika coast will affect the life of the coral reef ecosystem, one of which is the concentration of heavy metals that exceeds the quality standard limits which will be very dangerous for coral reefs. This study aims to determine the concentration of the heavy metals lead and cadmium in Porites lutea coral reefs in Kuta, Tanjung Aan and Gerupuk beaches. Research data collection (field and laboratory) was carried out in May 2023. Coral reef preparation was carried out at the Advanced and Analytical Biology Laboratory, FMIPA, University of Mataram and measurements of heavy metal content were carried out at the Environmental Laboratory, the West Nusa Tenggara Province Environment and Forestry Service. Measurement and calculation of heavy metal content using Atomic Absorption Spectrophotometry (AAS). The results showed that the concentrations of the heavy metals lead and cadmium in Porites lutea coral reefs are < 0.0005 mg/L and < 0.0001 mg/L, which are still below the quality standards (PPRI No.22 of 2021 concerning Sea water Wuality Standards on Marine Biota). The Bioaccumulation Factors (BAF) value in all samples of P. lutea coral in Mandalika coastal waters is 0.00 mg/L, this shows that there is no accumulation of heavy metals in P. lutea coral.